Simvastatin Blocks Reinstatement of Cocaine-induced Conditioned Place Preference in Male Mice with Brain Lipidome Remodeling - Wei Xu; Yuman He; Jiamei Zhang; Hongchun Li; Xuemei Wan; Menglu Li; Yonghai Wang; Rui Xu; Haoluo Zhang; Yanping Dai; Haxiaoyu Liu; Linhong Jiang; et al. (Neuroscience Bulletin, 2021)

Synthesis, characterization and antitumor mechanism investigation of ruthenium(II) polypyridyl complexes with artesunate moiety - Bi-Chun Chen; Jun-Jian Lu; Ning Jiang; Xiu-Rong Ma; Rong-Tao Li; Rui-Rong Ye (JBIC Journal of Biological Inorganic Chemistry, 2021)

cDNA cloning and expression analysis of glutaredoxin 3 in black tiger shrimp Penaeus monodon - Rui Fan; Yundong Li; Shigui Jiang; Song Jiang; Qibin Yang; Lishi Yang; Jianhua Huang; Falin Zhou (Aquaculture International, 2021)

A drug–biomarker interaction model to predict the key targets of Scutellaria barbata D. Don in adverse-risk acute myeloid leukaemia - Teng Wang; Chun-yi Lyu; Yue-hua Jiang; Xue-yan Dong; Yan Wang; Zong-hong Li; Jin-xin Wang; Rui-rong Xu (Molecular Diversity, 2021)

Qaidamihabitans albus gen. nov., sp. nov., a new member of the family Pseudonocardiaceae, and transfer of Prauserella shujinwangii to Qaidamihabitans gen. nov. as Qaidamihabitans shujinwangii comb. nov. - Li-Sha Tian; Gang-Qiang Jiang; Rui Li; Ping Ni; Chuan-En Li; Hong-Yan Zhang; Juan Wang; Xiao-Ping Zhang; Yun Wang; Shu-Kun Tang (Archives of Microbiology, 2021)

Generating broad-spectrum tolerance to ALS-inhibiting herbicides in rice by base editing - Rui Zhang; Sha Chen; Xiangbing Meng; Zhuangzhuang Chai; Delin Wang; Yuge Yuan; Kunling Chen; Linjian Jiang; Jiayang Li; Caixia Gao (Science China Life Sciences, 2021)

Glycomyces salinus sp. nov., an actinomycete isolated from a hypersaline habitat - Rui Li; Gang-Qiang Jiang; Yun Wang; Yi-Guang Chen; En-Min Zhou; Shu-Kun Tang (Archives of Microbiology, 2021)

Numerical modeling of 3D DC resistivity method in the mixed space-wavenumber domain - Shi-Kun Dai; Jia-Xuan Ling; Qing-Rui Chen; Kun Li; Qian-Jiang Zhang; Dong-Dong Zhao; Ying Zhang (Applied Geophysics, 2021)

Elevated pCO2 Impedes Succession of Phytoplankton Community From Diatoms to Dinoflagellates Along With Increased Abundance of Viruses and Bacteria - Ruiping Huang; Jiazhen Sun; Yunlan Yang; Xiaowen Jiang; Zhen Wang; Xue Song; Tifeng Wang; Di Zhang; He Li; Xiangqi Yi; Shouchang Chen; Nanou Bao; et al. (Frontiers in Marine Science, 2021)
Eutrophic coastal regions are highly productive and greatly influenced by human activities. Primary production supporting the coastal ecosystems is supposed to be affected by progressive ocean acidification driven by increasing CO 2 emissions. In order to investigate the effects of high p CO 2 (HC) on eutrophic plankton community structure and ecological functions, we employed 9 mesocosms and carried out an experiment under ambient (∼410 ppmv) and future high (1000 ppmv) atmospheric p CO 2 conditions, using in situ plankton community in Wuyuan Bay, East China Sea. Our results showed that HC along with natural seawater temperature rise significantly boosted biomass of diatoms with decreased abundance of dinoflagellates in the late stage of the experiment, demonstrating that HC repressed the succession from diatoms to dinoflagellates, a phenomenon observed during algal blooms in the East China Sea. HC did not significantly influence the primary production or biogenic silica contents of the phytoplankton assemblages. However, the HC treatments increased the abundance of viruses and heterotrophic bacteria, reflecting a refueling of nutrients for phytoplankton growth from virus-mediated cell lysis and bacterial degradation of organic matters. Conclusively, our results suggest that increasing CO 2 concentrations can modulate plankton structure including the succession of phytoplankton community and the abundance of viruses and bacteria in eutrophic coastal waters, which may lead to altered biogeochemical cycles of carbon and nutrients.

Alkalibacillus aidingensis sp. nov., an Bacterium Isolated from Aiding Lake in Xinjiang Province, North-West China - Rui Li; Li Yang; Rüdiger Pukall; Meina Neumann-Schaal; Chang-Gai Mu; Yong-Jiang Shi; Yun Wang; Gang-Qiang Jiang; Yu-Guang Zhou; Man Cai; Min Yin; Wen-Yong Zhu; et al. (Current Microbiology, 2021)

Screening and Analysis of Multiclass Veterinary Drug Residues in Animal Source Foods using UPLC-Q-Exactive Orbitrap/MS - Wentao Zhao; Rui Jiang; Wenping Guo; Chao Guo; Shilei Li; Juanqiang Wang; Shouwei Wang; Yingying Li (Bulletin of Environmental Contamination and Toxicology, 2021)
A rapid, simple, and sensitive method of detecting veterinary drug residues in animal food sources, including poultry and pork, was developed and validated. The method was optimized for over 155 veterinary drugs of 21 different classes. Sample pretreatment included a simple solid-liquid extraction step with 0.2% formic acid-acetonitrile-water and a purification step with a PRiME HLB (hydrophile-lipophile balance) solid-phase extraction cartridge. Data were collected using ultra-high-performance liquid chromatography coupled to Quadrupole-Exactive Orbitrap mass spectrometry. The limits of detection of 155 veterinary drugs ranged from 0.1 µg/kg to 10 µg/kg. The recovery rates were between 79.2 and 118.5 % in all matrices studied, with relative standard deviation values less than 15% (n = 6). The evaluated method allows the reliable screening, quantification, and identification of 155 veterinary drug residues in animal source food and has been successfully applied in authentic samples.

Heterogeneity of tight sandstone reservoirs based on fractal theory: the Xu-6 member of Xujiahe Formation in Guang'an area, central Sichuan Basin - Fang Shen; Liang Yue; Ziliang Liu; Wei Yang; Kaarel Mänd; Hui Jin; Fengjie Li; Yue Zhou; Minghe Zhang; Rui Jiang (Arabian Journal of Geosciences, 2021)

Longitudinal associations of sleep duration and sleep quality with coronary heart disease risk among adult population: classical meta-analysis and Bayesian network meta-analysis - Rui Zeng; Yu-ting Jiang; Tian-wu Chen; Dan-dan Guo; Rui Li (Sleep and Biological Rhythms, 2021)

A new dineolignan with anti- β -amyloid aggregation activity from the fruits of crataegus pinnatifida bge - Peng Zhao; Li-Li Lou; Hao Zhang; Rui Guo; Xiao-Bo Wang; Xiao-Xiao Huang; Shao-Jiang Song (Natural Product Research, 2021)

Using the Metabolome to Understand the Mechanisms Linking Chronic Arsenic Exposure to Microglia Activation, and Learning and Memory Impairment - Rui-Yuan Zhang; Jie-Bai Tu; Rui-Tu Ran; Wen-Xuan Zhang; Qiang Tan; Ping Tang; Tao Kuang; Shu-Qun Cheng; Cheng-Zhi Chen; Xue-Jun Jiang; Chang Chen; Ting-Li Han; et al. (Neurotoxicity Research, 2021)

Antifungal Effect of Long Noncoding RNA 9708-1 in the Vulvovaginal Candidiasis Murine Model - Ying Wu; Lisha Jiang; Lingling Zhang; Xia Liu; Lina Yan; Ting Luan; Can Rui; Zhiyuan Mao; Chong Fan; Yu Liu; Ping Li; Xin Zeng (Mycopathologia, 2021)
Vulvovaginal candidiasis (VVC) caused by Candida spp. affects 70–75% of women at least once during their lives. We aim to elucidate the potential mechanism of VVC and investigate the therapeutic effects of long noncoding RNA 9708-1. Female BALB/c mice were randomized to four treatment groups, including the blank control group, VVC control group, vehicle control group and lncRNA 9708-1-overexpressed group. Mice were euthanized on Day 4, Day 7 and Day 14 after treatment. Colony-forming unit (CFU) was measured, and the inflammation was detected by hematoxylin and eosin (H&E). Gene and protein expression levels of lncRNA 9708-1 and FAK were determined by real-time PCR, Western blot and immunohistochemistry. The overexpression of lncRNA 9708-1 significantly decreased the fungal load from Day 4 to 7. H&E staining indicated that the impaired histological profiles were improved in lncRNA 9708-1-overexpressed group. LncRNA 9708-1 led to a significant increase in FAK level of vagina tissue which is expressed mainly in epithelial basal layer. This study suggests that lncRNA 9708-1 played a protective role on murine experimental VVC by upregulating the expression levels of FAK.

Experimental validation of a new semi-empirical impact force model of the dry granular flow impact against a rigid barrier - Yuan-Jun Jiang; Xiao-Yi Fan; Li-Jun Su; Si-you Xiao; Jing Sui; Rui-Xiao Zhang; Yue Song; Zhi-Wen Shen (Landslides, 2021)

Isolation, characterization, and application of Salmonella paratyphi phage KM16 against Salmonella paratyphi biofilm - Liming Jiang; Rui Zheng; Qiangming Sun; Chenghua Li (Biofouling, 2021)

Abiotic and biotic controls of soil dissolved organic nitrogen along a precipitation gradient on the Tibetan plateau - Lili Jiang; Shiping Wang; Zhe Pang; Changshun Wang; Fandong Meng; Zhichun Lan; Xiaoqi Zhou; Yaoming Li; Zhenhua Zhang; Caiyun Luo; Davey L. Jones; Yichao Rui; et al. (Plant and Soil, 2021)

GmNAC06, a NAC domain transcription factor enhances salt stress tolerance in soybean - Ming Li; Rui Chen; Qiyan Jiang; Xianjun Sun; Hui Zhang; Zheng Hu (Plant Molecular Biology, 2021)
Key message We found GmNAC06 plays an important role in salt stress responses through the phenotypic, physiological and molecular analyses of OE, VC, and Mutant composite soybean. Abstract Salinization affects 20% of all cultivated land worldwide because of the high salinity of irrigation water and the excessive use of water, and this amount is increasing daily. NAC (NAM, ATAF, and CUC) have been found to be involved in salt stress. In this study, a soybean NAC gene, GmNAC06 (Glyma06g21020.1), was cloned and functionally characterized. The results of expression analysis suggested that salt stress could influence the expression level of GmNAC06 . The subcellular localization analysis results suggested that GmNAC06 may function as a transcription factor. Under salt stress, the overexpression technology combined with CRISPR-Cas9 system found that GmNAC06 could cause the accumulation of proline and glycine betaine to alleviate or avoid the negative effects of ROS; similarly, it could control the Na + /K + ratios in hairy roots to maintain ionic homeostasis. The fresh weight of the transgenic hairy roots and the histochemical ROS staining of wild leaves suggested that transgenic hairy roots influence the function of wild leaves under salt stress conditions. Moreover, the expression levels of GmUBC2 and GmHKT1 were higher in the GmNAC06 hairy roots than in the control. Thus, the overexpression of GmNAC06 in hairy roots notably causes an entire composite plant to exhibit salt tolerance. The phenotype of composite soybean plants and transgenic Arabidopsis plants suggest that GmNAC06 plays a role in response to salt stress and could be useful in generating salt tolerant transgenic crops.

Combining forecast of landslide displacement based on chaos theory - Xunchang Li; Chao Jiang; Rui Xu; Wei Yang; HaoHao Wang; Yu Zou (Arabian Journal of Geosciences, 2021)